Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content:1. A Glimpse into the Future of Quantum Computing and AIEng. Fayyad Mohammed Hani Bayan2. Designing a Hybrid System based on between Deep learning Network with Face Detection algorithm for Emotion Recognition through Facial Features AnalysisMohamad Bashir Amir Nahas, Asst-Prof. Lara Fathi Kadid, lecturer \ Mohamad Ahmad Mounir Batikh3. Deductive analysis for Municipalities of Baghdad city, within the healthy city programDr. Heyam Hameed Abdul-majeed Ali4. Preparing a cost control plan for a contracting company VR:00 (05-2019)Eng. Mohamad Muhanad Ahmad Senjab5. Evaluation of design quality and its impact on execution in private housing projects  in KuwaitEng. Sadeq Yahya Bumejdad, Eng. Mohamed Ezzat Elnakhely6. Investigating the Water Demand and Supply Situation in Baljurashi Governorate,  Saudi ArabiaDr. Gamal Khalid Awadelkarim Mohamed, Dr. Osman Mohamed Najjar Ali, Dr. Ali Khalaf Ahmed Al-Baggar, Prof. Hasan Saad Mohammed Hilmi7. Review on building energy effeciency through optimized building envelopesMs. Maryam Omar Bazaraah, Prof. Laila Khodeir, Dr. Mahmoud Gadelhak8. Requirements to Improve the Technical Support at Umm Al-Qura University (2019) (Concept Proposal)Eng. Reem Metlea Mohamed Alqahtani, Eng. Reham Zahir Omar Almarghlani
Keywords: Journal of Engineering Sciences and Information Technology